Profile of Single Mode Fiber Coupler Combining with Bragg Grating - Romi Fadli Syahputra; Saktioto Saktioto; Ros Meri; Syamsudhuha Syamsudhuha; Okfalisa Okfalisa (Universitas Ahmad Dahlan, 2017)
This paper describes a numerical experiment of design and operation of a fiber coupler between single mode fiber and fiber Bragg grating (FBG). Both components are coupled depending with optical waveguide and source parameters. A characterization of fiber coupler is simulated by varying long grating of 10 mm to 60 mm using transfer matrix method based on coupled mode equation. The wave peak, transmission, and dispersion parameters are analyzed to determine the performance of the fiber coupler. The transmission spectrum showed the wave peaks rise to any increase in the grating length on channel 1 and channel 2. Transmission on channel 1 and channel 2 decreased from the wavelength range of 1.45μm–1.55μm and rised in the range of 1,55μm–1,65μm for each increment in length of grating. The dispersion showed the zero dispersion at specific wavelength for each increase in length of grating. This component can be applied for controlling information signal in wide range communication.